Two new species of the rare genus Nygolaimoides Meyl in Andrássy, 1960 (Nematoda, Dorylaimida, Thorniidae) from Iran, with a compendium of its species - Asl, Ebrahim Zahedi; Niknam, Gholamreza; Jabbari, Habibeh; Pena-Santiago, Reyes (Zootaxa, 2016)
Two new Nygolaimoides species are described and illustrated from soil and stumps of an old nursery of Populus alba, Miandoab County, West Azarbaijan province, Iran. Nygolaimoides zarrinensis sp. n. is characterized by its 0.73–0.94 mm long body, lip region 9.5–10.5 µm broad, odontostyle 9.5–11.0 µm long, neck length 162–194 µm long, pharyngeal expansion 78–83 µm long, V = 46–50, female tail short and rounded conoid (11–15 µm, c = 63–84, c’ = 0.7–0.9), male tail rounded conoid (14–18 µm, c = 43–55, c’ = 0.9–1.1), spicules 21–25 µm long and with irregular head, and two ventromedian supplements bearing hiatus. Nygolaimoides albus sp. n. is distinguished by its 0.64–0.95 mm long body, lip region 8–10 µm broad, odontostyle 9.5–11.0 µm long, neck length 164–200 µm long, pharyngeal expansion 66–72 µm long, V = 43–51, female tail hemispheroid (4.0–5.5 µm, c = 120–233, c’ = 0.4–0.7), male tail conoid (9.0–12.0 µm, c = 58–78, c’ = 0.7–1.0), spicules 13–17 µm long, and two ventromedian supplements bearing hiatus. SEM observations have been made for the first time for representatives of this genus. The taxonomy of the genus is updated with a list of its species, a key to their identification and a table-compendium of relevant morphometrics.